2014
DOI: 10.1002/art.38249
|View full text |Cite
|
Sign up to set email alerts
|

Critical Role of Endoplasmic Reticulum Aminopeptidase 1 in Determining the Length and Sequence of Peptides Bound and Presented by HLA–B27

Abstract: Objective. HLA-B27 and endoplasmic reticulum aminopeptidase 1 (ERAP1) are the two strongest genetic factors predisposing to ankylosing spondylitis (AS). A key aminopeptidase in class I major histocompatibility complex presentation, ERAP1 potentially contributes to the pathogenesis of AS by altering HLA-B27 peptide presentation. The aim of this study was to analyze the effects of ERAP1 on the HLA-B27 peptide repertoire and peptide presentation to cytotoxic T lymphocytes (CTLs).Methods. ERAP1-silenced and -compe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
66
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 74 publications
(73 citation statements)
references
References 41 publications
6
66
0
1
Order By: Relevance
“…The effect impacts mainly the P1 residue and, to a lesser extent, the remaining peptide sequence, the peptide length, the amount of specific ligands and the B27 affinity and thermostability of the overall peptide/B27 complexes. It is noteworthy that another study has shown that ERAP1 silencing, as expected, decreased the amount of B27-bound nonamer peptides and, interestingly, increased the number of longer ligands, especially with extended C-terminus [91].…”
Section: Hla-b27 and Erap1/2 As Players In Ankylosing Spondylitissupporting
confidence: 73%
See 2 more Smart Citations
“…The effect impacts mainly the P1 residue and, to a lesser extent, the remaining peptide sequence, the peptide length, the amount of specific ligands and the B27 affinity and thermostability of the overall peptide/B27 complexes. It is noteworthy that another study has shown that ERAP1 silencing, as expected, decreased the amount of B27-bound nonamer peptides and, interestingly, increased the number of longer ligands, especially with extended C-terminus [91].…”
Section: Hla-b27 and Erap1/2 As Players In Ankylosing Spondylitissupporting
confidence: 73%
“…Interestingly, the decreased CTL recognition of the cells expressing the Arg528 ERAP1 variant or the minigenes containing KK10 precursors was reversed by the combination Arg528/730Glu, supporting the concept that the global ERAP1 haplotype modulates the fine enzymatic specificity [91].…”
Section: Hla-b27 and Erap1/2 Interplay In The Anti-viral Immunitymentioning
confidence: 64%
See 1 more Smart Citation
“…Differences in trimming properties may predispose an individual to the formation of ER B27 2 and UPR. In addition, the generation of suboptimal HLA-B27 ligands created by aberrant ERAP1 activity that bind with sufficient affinity to pass intracellular quality control (16,29) may dissociate rapidly at the cell surface, leading to increased aberrant forms of B27. These mechanisms are not necessarily mutually exclusive, nor do they preclude other possible mechanisms such as the ability of different ERAP1 variants to generate specific arthritogenic peptides.…”
Section: Discussionmentioning
confidence: 99%
“…Heterozygous ERAP-1 +/− mice showed an intermediate phenotype that suggest polymorphisms that affect ERAP-1 function could affect antigen presentation (17). ERAP-1 has recently been shown to be associated with anklyosing spondylitis, a condition strongly linked to another HLA class I molecule: HLA-B*27 (18). The relevance of these findings to BD includes the possibility that different peptides binding in the groove could either activate a different population of CD8 +ve cells or stabilize HLA molecules on the surface, potentially increasing the inhibitory signal to NK cells.…”
Section: Functional Role Of Hla-b*51 In Bdmentioning
confidence: 99%